Japanese guidelines for the management of acute pancreatitis: Japanese Guidelines 2015 - Yokoe, Masamichi; Takada, Tadahiro; Mayumi, Toshihiko; Yoshida, Masahiro; Isaji, Shuji; Wada, Keita; Itoi, Takao; Sata, Naohiro; Gabata, Toshifumi; Igarashi, Hisato; Kataoka, Keisho; Hirota, Masahiko; et al. (Journal of hepato-biliary-pancreatic sciences, 2015)
Background Japanese (JPN) guidelines for the management of acute pancreatitis were published in 2006. The severity assessment criteria for acute pancreatitis were later revised by the Japanese Ministry of Health, Labour and Welfare (MHLW) in 2008, leading to their publication as the JPN Guidelines 2010. Following the 2012 revision of the Atlanta Classifications of Acute Pancreatitis, in which the classifications of regional complications of pancreatitis were revised, the development of a minimally invasive method for local complications of pancreatitis spread, and emerging evidence was gathered and revised into the JPN Guidelines. Methods A comprehensive evaluation was carried out on the evidence for epidemiology, diagnosis, severity, treatment, post‐endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis and clinical indicators, based on the concepts of the GRADE system (Grading of Recommendations Assessment, Development and Evaluation). With the graded recommendations, where the evidence was unclear, Meta‐Analysis team for JPN Guidelines 2015 conducted an additional new meta‐analysis, the results of which were included in the guidelines. Results Thirty‐nine questions were prepared in 17 subject areas, for which 43 recommendations were made. The 17 subject areas were: Diagnosis, Diagnostic imaging, Etiology, Severity assessment, Transfer indication, Fluid therapy, Nasogastric tube, Pain control, Antibiotics prophylaxis, Protease inhibitor, Nutritional support, Intensive care, management of Biliary Pancreatitis, management of Abdominal Compartment Syndrome, Interventions for the local complications, Post‐ERCP pancreatitis and Clinical Indicator (Pancreatitis Bundles 2015). Meta‐analysis was conducted in the following four subject areas based on randomized controlled trials: (1) prophylactic antibiotics use; (2) prophylactic pancreatic stent placement for the prevention of post‐ERCP pancreatitis; (3) prophylactic non‐steroidal anti‐inflammatory drugs (NSAIDs) for the prevention of post‐ERCP pancreatitis; and (4) peritoneal lavage. Using the results of the meta‐analysis, recommendations were graded to create useful information. In addition, a mobile application was developed, which made it possible to diagnose, assess severity and check pancreatitis bundles. Conclusions The JPN Guidelines 2015 were prepared using the most up‐to‐date methods, and including the latest recommended medical treatments, and we are confident that this will make them easy for many clinicians to use, and will provide a useful tool in the decision‐making process for the treatment of patients, and optimal medical support. The free mobile application and calculator for the JPN Guidelines 2015 is available via http://www.jshbps.jp/en/guideline/jpn‐guideline2015.html